Drug Use among Iranian Drivers Involved in Fatal Car Accidents - Assari, Shervin; Moghani Lankarani, Maryam; Dejman, Masoumeh; Farnia, Marzieh; Alasvand, Ramin; Sehat, Mahmood; Roshanpazooh, Mohsen; Tavakoli, Mahmood; Jafari, Firoozeh; Ahmadi, Khodabakhsh (Frontiers in Psychiatry, 2014)
Background: Although the problem of substance use among drivers is not limited to a special part of the world, most published epidemiological reports on this topic is from industrial world. Aim: To determine drug use among Iranian adults who were imprisoned for vehicle accidents with fatality. Methods: This study enrolled 51 Iranian adults who were imprisoned for vehicle accidents with fatality. This sample came from a national survey of prisoners. Data was collected at entry to prisons during the last 4 months of 2008 in 7 prisons in different parts of the country. Self reported drug use was registered. Commercial substance use screening tests were also done. Results: Drug test was positive for opioids, cannabis and both in 37.3%, 2.0% and 13.7%, respectively. 29.4% tested positive for benzodiazepines. Using test introduced 23.5% of our sample as drug users, who had declined to report any drug use. Conclusion: Opioids are the most used illicit drug in the case of vehicle accidents with fatality, however, 20% of users do not declare their use. This high rate of drug use in vehicle accidents with fatality reflects the importance of drug use control as a part of injury prevention in Iran. There might be a need for drug screening after severe car accidents.